HIV/AIDS Induced Suffering in Africa: An Interpretative Reflection from Pauline Christology (Hekima Review, 2009)
Suffering is part of the mysterious realities of life. The efforts to understand it does not remove or reduce it. Rather, attempts at comprehension help to proffer different views which enable humanity to accept suffering with hope. In contemporary Africa, the reality of suffering induced by HIV/AIDS is so evident that one needs deep reflections to appreciate its true import. This is the main task of this article. I shall explore Pauline Christology as a paradigm of a deeper reflection that attempts to show the unfathomable level of despair that people live in when one tests sero-positive. For this purpose, I shall make use of the shared experiences of a Kenyan woman who is sero-positive, and works with people that are infected. Bringing together Pauline understanding of Christ and the level of suffering shared by sufferers, we are empowered to be empathetic at a different level that is never talked about in the popular discussions around the malady.